Frontierism, intellectual listeners and the new European wave: On the reception of Dutch jazz in DownBeat, 1960–1980 - Rusch, Loes (Jazz Research Journal, 2015)
This article engages with the understanding of non-American jazz practices and the global spread of jazz from an American mainstream perspective, through a critical investigaton of the mediation of Dutch and European jazz in the American jazz magazine Down Beat. It explores the role and function of some of the key actors through which the story of European jazz is told; correspondents, American musicians visiting and migrating Europe, European musicians, and European audiences. By exposing underlying defining notions, such as “jazz as an essentially American music practice” and “the intellectual European,” this essay demonstrates how local, non-American jazz practices in Down Beat during the 1960s and 1970s are understood—misunderstood, perhaps—in terms of equality rather than in differentiating terms in comparison with the American jazz tradition.